Un Manfred di troppo. Fortuna di un’opera non rappresentabile in Francia tra Ottocento e Novecento - Leonardo Mancini (Annali Online dell'Università di Ferrara. Sezione Lettere, 2017)
The essay focuses on four different mise-en-scène of the Manfred by Lord Byron with musics by Schumann which took place in France between 1886 and 1912, thanks to four different protagonists of the French and European theatre of those years: Jean Mounet-Sully, Aurélien Lugné-Poe, Adolphe Appia, and Émile Moreau. Using their peculiar qualities as actors and directors, each of them found in the Manfred, a poem which was originally intended by Lord Byron as not to be staged, an opportunity to discover new areas of experimentation in their artistic and theatrical careers: the musicality of the declamation for Mounet-Sully, the research on new theatrical languages for Lugné-Poe, the uses of lights and stage design for Appia, and the relations between opera, music and spoken text for Moreau.